The association between the prevalence of cigarette smoking and complications in patients with type 2 diabetes - Onalan, Erhan; Gozel, Nevzat (Mattioli 1885, 2020)
Background: This study including diabetic individuals from Elazig province of Turkey was undertaken to assess the association between complication risk and the prevalence of cigarette smoking, a growing public health problem and a major cause of morbidity and mortality worldwide. Methods: In this descriptive cross-sectional study, a total of 300 patients (150 male, 150 female) attending to our outpatient unit with a diagnosis of Type 2 DM between May 2018 and October 2018 were included. History of cigarette smoking, educational level, presence of complications and demographic characteristics, systolic and diastolic blood pressure, and family history were recorded. Demographic data of interest included age, gender, waist and hip circumference, and the body mass index. Results of biochemistry tests were collected from routine investigations. All statistical analyses were performed using a statistical software pack (SPSS 22.0). Quantitative data were analyzed with the t-test, while categorical data were examined using chi-square test. The results were expressed with 95% confidence intervals at a significance level of p < 0.05. Results: Of the 300 participants, 77 (25%) were current smokers. Male and elderly patients were more likely to be smokers, who had a lower BMI. A significant and inverse association between cigarette use and BMI was observed (p < 0.01). Smokers had significantly higher HbA1c, triglyceride, and LDL (p < 0.01, p < 0.01, and p < 0.01, respectively). Hypertension, level of education, duration of diabetes, and the presence of neuropathy, nephropathy, or retinopathy were not significantly associated with smoking, while coronary artery disease showed a significant association (p < 0.01). Conclusion: Approximately one fourth (25%) of this diabetic cohort was smokers, who had significantly increased occurrence of coronary artery disease. Also smokers had significant elevations in LDL, triglycerides, and HbA1c as compared to non-smokers.
Keywords: cigarette smoking; diabetes mellitus; Elazig